PARP Inhibitor in Platinum-Resistant Ovarian Cancer: Single-Center Real-World Experience. (2021) - Agarwal, Amit; Baghmar, Saphalta; Dodagoudar, Chandragouda; Qureshi, Suhail; Khurana, Aseem; Vaibhav, Vikas; Kumar, Guresh
Abstract : PURPOSE: Poly (ADP-ribose) polymerase inhibitors (PARPi) have proven efficacy in treatment of BReast CAncer ( BRCA ) gene mutation-positive platinum-sensitive ovarian cancers. There is paucity of data for their role in platinum-resistant ovarian cancer (PROC). We report here retrospective analysis of outcome of PARPi treatment in a group of patients including those of PROC. PATIENTS AND METHODS: We analyzed all consecutive patients who received PARPi. The efficacy of PARPi monotherapy was assessed in patients with relapsed high-grade serous ovarian carcinoma with g BRCA m. The drug was procured through compassionate program. Drugs (olaparib and talazoparib) were provided in capsule form. RESULTS: Between July 1, 2015, and June 30, 2019, 28 patients with ovarian cancer received PARPi. At the time of data censoring (September 30, 2019), four (14.3%) patients are still on treatment. Median age was 54.5 years (range, 39-75 years). Median number of previous lines of chemotherapy received was three (range, 1-6). Eleven platinum-sensitive patients received the drug as maintenance (five in complete response and six in partial response after chemotherapy), whereas 17 (60.7%) had platinum-resistant progressive disease while starting the drug. In PROC, objective response rate (complete response plus partial response) was 47%, median progression-free survival was 8.2 months (5.3-11.3), and overall survival was 14.9 months (11.2-18.5). No new side effects were observed. CONCLUSION: This is the first study from India evaluating PARPi in platinum-resistant ovarian cancer. This study suggests that PARPi is a viable treatment option in patients with PROC with gBRCAm. This should be further evaluated in randomized clinical trial.